Stable n-type thermoelectric multilayer thin films with high power factor from carbonaceous nanofillers. (October 2016) - Cho, Chungyeon; Culebras, Mario; Wallace, Kevin L.; Song, Yixuan; Holder, Kevin; Hsu, Jui-Hung; Yu, Choongho; Grunlan, Jaime C.
Abstract: High power factor n-type organic thermoelectric nanocomposites are assembled by alternately depositing double walled-nanotubes (DWNT), stabilized by polyethyleneimine (PEI), and graphene stabilized by polyvinylpyrrolidone (PVP), from water using the layer-by-layer (LbL) assembly technique. This unique combination of carbon nanomaterials exhibits an electrical conductivity of 300 S cm −1 and a relatively stable power factor of 190 μW m −1  K −2 at room temperature. Graphical abstract: Highlights: Thermoelectric properties of n-type organic nanocomposites are characterized. An DWNT and graphene-based thin film has PF of 190 μW m −1  K −2 and is quite air-stable. A DWNT/graphene multilayer nanocomposite thin film has conductivity of 300 S/cm.